2020
DOI: 10.1520/jte20190224
|View full text |Cite
|
Sign up to set email alerts
|

Study on Workability and Skid Resistance of Bio-Oil–Modified Fog Seal with Sand

Abstract: The objective of this study is to evaluate different fog seal materials, including Tianjin BEST - micro-seal bonding reductant (BEST-MBR), American MasterSeal, and a newly designed bio-oil–modified fog seal with sand (BFSS) using various sand contents. The workability of all materials was tested based on the fluidity test, seepage performance test, and the indoor skid resistance test. A new method to evaluate the surface texture of solidified fog seal with sand (FSS) material was performed based on the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Research by Hu et al [9] showed that the water-based epoxy resin in the water-based epoxy asphalt modified emulsion (WEB) can significantly improve the skid resistance and durability of the fog-sealed pavement. Feng et al [10] evaluated the skid resistance performance of the Tianjin BEST microsealing bonding reductant, the American Master seal, and a new type of bio-oil modified fog seal with sand based on an aggregate image. Measurement System II is a new method for evaluating the surface characteristics of solid fog seals with sand materials.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Hu et al [9] showed that the water-based epoxy resin in the water-based epoxy asphalt modified emulsion (WEB) can significantly improve the skid resistance and durability of the fog-sealed pavement. Feng et al [10] evaluated the skid resistance performance of the Tianjin BEST microsealing bonding reductant, the American Master seal, and a new type of bio-oil modified fog seal with sand based on an aggregate image. Measurement System II is a new method for evaluating the surface characteristics of solid fog seals with sand materials.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the road performance of a fog seal mainly focuses on the four aspects of skid resistance, permeability, wear resistance, and aging resistance. Fog seal will fill a part of the gap after it is used on the pavements surface, thus reducing the skid resistance of the pavements surface [14]. The skid resistance in pavements is a vital factor for any road administration because with higher friction available, drivers can better control their vehicles [15,16], the decrease of skid resistance will lead to the decrease of road safety.…”
Section: Introductionmentioning
confidence: 99%
“…Cui [24] explored the feasibility for using silicone resin polymer in fog seal maintenance. Feng [25] tested the practical application possibility by mixing various contents of sand with modified bio-oil. Wan [26] investigated the chemical structure and rheological properties of aged styrene-butadiene-styrene modified asphalt with two kinds of rejuvenator materials, and thought that high maltene content could significantly soften the aged binder.…”
Section: Introductionmentioning
confidence: 99%